PENGARUH MEKANISME CORPORATE GOVERNANCE DAN KINERJA INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN - Izlin Pratiwi; Lukman Effendy; Widia Astuti (Universitas Dharmawangsa, 2023)
The purpose of this study was to determine how corporate governance mechanisms (number of boards of directors, proportion of independent commissioners, ownership concentration and number of audit committees) and intellectual capital performance affect the financial performance of manufacturing companies listed on the IDX in 2019-2021. The quantitative approach used in conducting this research. The sample used was 129 manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021 which became the focus of this study using secondary data. The panel data regression model is used to measure the dependent variable, namely Return on Asset (ROA). While the independent variables are the number of boards on directors, the proportion of independent commissioners, ownership concentration and the number of audit committees and intellectual capital. Purposive sampling as a sampling technique. This study uses the E-Views version 10 program for panel data regression analysis as a data analysis technique. The test results show that the company's financial performance is influenced by intellectual capital, but not by the number of boards on directors, the proportion of independent commissioners, ownership concentration and the number of audit committees.